Application of composite layered repair system using titanium mesh, bone cement and vacuum sealing drainage for chest wall defect - Liu, Gaofeng; Ding, Xiaoyong; Li, Qingyuan; Chu, Xia; Deng, Yingbiao; Cui, Sujuan; Zhou, Li; Xing, Chaofeng; Sun, Xiaohang; Zhang, Jie (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the therapeutic efficacy of a composite layered repair system utilizing titanium mesh (TM), bone cement (BC) and vacuum sealing drainage (VSD) for chest wall defect reconstruction, providing a reliable theoretical foundation and practical guidance for clinical chest wall trauma management.MethodA thoracic defect model (≥6 × 6 cm2) was established in 22 adult goat and then divided into the TM + BC + VSD, TM + BC and TM + VSD groups. The survival status, activity status, wound recovery, vital signs, blood routine, arterial blood gas and inflammatory factor levels of the three goat groups were monitored and compared after the operation.ResultAll groups demonstrated comparable survival rates and periods with satisfactory defect repair outcomes. The PaO2 at multiple time points after surgery in the TM + BC + VSD group were higher than those in the TM + BC and TM + VSD groups, while the activity status score, WBC and levels of PaCO2, IL-2, IL-6, IL-10, IL-17 and TNF-α were lower than those in the TM + BC and TM + VSD groups. The SpO2, hemoglobin and erythrocyte were higher than those in the TM + VSD group, and the wound healing score, heart rate was lower than that in the TM + VSD group.ConclusionThe composite laminated repair system constructed by TM, BC and VSD can increase the survival rate after chest wall defect repair, promote functional recovery, improve oxygenation and reduce inflammatory responses, and has potential clinical application value.